2015
DOI: 10.1088/0953-2048/28/7/075012
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic flux avalanches and the accompanied thermal strain in type-II superconducting films: effect of magnetic field ramp rate

Abstract: Dendritic flux avalanches and the accompanying thermal stress and strain in type-II superconducting thin films under transverse magnetic fields are numerically simulated in this paper. The influence of the magnetic field ramp rate, edge defects, and the temperature of the surrounding coolant are considered. Maxwell's equations and the highly nonlinear E-J powerlaw characteristics of superconductors, coupled with the heat diffusion equation, are adopted to formulate these phenomena. The fast Fourier transform-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…We also show that the curvature of the d-lines emerging from the defect decreases as the temperature is increased. Moreover, in opposition to what has been repeatedly suggested based on the Bean model, [2][3][4]13 indentations do not seem to be distinguished places for the nucleation of flux jumps but rather the opposite, a place where flux avalanches will not take place. The extension of our results to samples with defects inside rather than at the border of the films is straightforward.…”
mentioning
confidence: 68%
“…We also show that the curvature of the d-lines emerging from the defect decreases as the temperature is increased. Moreover, in opposition to what has been repeatedly suggested based on the Bean model, [2][3][4]13 indentations do not seem to be distinguished places for the nucleation of flux jumps but rather the opposite, a place where flux avalanches will not take place. The extension of our results to samples with defects inside rather than at the border of the films is straightforward.…”
mentioning
confidence: 68%
“…It has been suggested that the system of weakly pinned vortices resembles the pinned CDW state. Experimental results on charge density waves gives that coherent current or voltage oscillations appear along the sample after reaching the threshold value of the driving voltage or current [15][16][17][18][19]. In the present study, we suppose that a physical mechanism regarding the density instabilities of flux lines (or self magnetic field (SMF) lines) can be introduced as a possible mechanism for coherent voltage oscillations.…”
Section: Relationship Between Voltage Oscillations and Charge Densitymentioning
confidence: 85%
“…Our numerical simulation region is 2 L × 2 L, where L = 1.3a [17]. The simulation region is discretized with 512 × 512 equidistant grids.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers have done much work on different superconducting materials to understand the characteristics of flux avalanche. Flux avalanche is closely related to the external magnetic field [13,14], the geometry of the superconducting material [15,16], the field ramp rate [17] and the environmental temperature [18]. Baziljevich et al [19] studied the dendritic instability in a YBa 2 Cu 3 O 7-d film at very high magnetic ramp rates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation